Retrato de la familia Vargas Ramírez (1945)
De izquierda a derecha: de pie está Alfredo Vargas, Enrique Vargas, Carlos Vargas, Manuel José Vargas. Sentados están Margarita Ramírez de Vargas, Juan José Vargas, Margarita Vargas, Manuel José Vargas